The Advantages and Disadvantages of Using Chat GPT for Writing Skill in Higher School (Conference on English Language Teaching, 2024)
Chat generative process training (ChatGPT) is a generative machine learning technique that can be used to analyze and process enormous number of data to accomplish responses to a set of questions. This research would focus on the advantages, and disadvantages of chat GPT especially for language learning, especially for writing skills in a higher school level. The material for this study was obtained from digital media and scientific repositories. Chat GPT is important for research, especially helping to come up with ideas for articles; it also has challenges such as data quality, ethical issues, or the challenge for the students' critical thinking (Fuchs, 2023). This study would also focus on how ChatGPT can improve students' writing skills.